2014
DOI: 10.1002/2014jc009839
|View full text |Cite
|
Sign up to set email alerts
|

Wave-driven along-channel subtidal flows in a well-mixed ocean inlet

Abstract: Observations of waves, flows, and water levels collected for a month in and near a long, narrow, shallow ($ 3000 m long, 1000 m wide, and 5 m deep), well-mixed ocean inlet are used to evaluate the subtidal (periods > 30 h) along-inlet momentum balance. Maximum tidal flows in the inlet were about 1.5 m/s and offshore significant wave heights ranged from about 0.5 to 2.5 m. The dominant terms in the local (across the km-wide ebb shoal) along-inlet momentum balance are the along-inlet pressure gradient, the botto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 71 publications
8
51
0
Order By: Relevance
“…12b, black curve). These gradients computed using wave parameters derived from the spectral peak are consistent with those computed using the centroidal (energy weighted) frequency and direction (Wargula et al 2014). In particular, both remotely sensed and in situ estimates have onshore (positive) forcing during the high-wave conditions (Fig.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…12b, black curve). These gradients computed using wave parameters derived from the spectral peak are consistent with those computed using the centroidal (energy weighted) frequency and direction (Wargula et al 2014). In particular, both remotely sensed and in situ estimates have onshore (positive) forcing during the high-wave conditions (Fig.…”
supporting
confidence: 68%
“…The spatial wave transformation and hence, the radiation-stress gradients, are affected by refraction and shoaling, and are modulated by dissipation in and around the surfzone (Svendsen 2006). Recent in situ observations of waves and currents at the tidal inlet investigated here (Wargula et al 2014) demonstrated that the breaking-induced gradient of the cross-shore radiation stress contributed significantly to the subtidal alongchannel momentum balance, enhancing the flood flows into the inlet, particularly during storms, similar to results at other inlets (Malhadas et al 2009;Bertin et al 2009;Dodet et al 2013;Orescanin et al 2014).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Wargula et al, 2014). At the main channel, the flow is also subdivided in two sections, one over the ebb-tidal delta lobe and another directed seaward.…”
Section: Discussionmentioning
confidence: 99%
“…Different processes caused by waves promote flood dominance (e.g. Bertin et al, 2009;Nahon et al, 2012;Wargula et al, 2014). We expect that the inclusion of more wave processes on sediment transport would lead to faster development towards equilibrium by stimulating flood-directed transport.…”
Section: Comparison To Real Estuariesmentioning
confidence: 99%